2005
DOI: 10.1002/hep.20855
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of smooth pursuit eye movements in cirrhosis: Relationship to hepatic encephalopathy and its treatment

Abstract: Smooth pursuit eye movements (SPEM) are the conjugate movements used to track the smooth trajectory of small dots. Jerky or 'saccadic' ocular pursuit has been reported in patients with cirrhosis, but no formal assessment of SPEM has ever been undertaken. The aim of this study was to evaluate SPEM in patients with cirrhosis and varying degrees of hepatic encephalopathy. The patient population comprised 56 individuals (31 men, 25 women) of mean age 51.1 (range, 25-70) years, with biopsy-proven cirrhosis, classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…It was agreed that patients with a history of overt HE or treatment exposure should be excluded from these trials as treatment status has a significant confounding effect on the classification of neuropsychiatric performance. 34 Patients with overt HE may show few, if any, clinical abnormalities following treatment but retain some degree of neuropsychometric or neurophysiological impairment in the longer term. 3,35,36 These patients may be classified as having minimal HE but their responses to treatment will differ substantially from those diagnosed as having minimal HE de novo.…”
Section: Secondary Prophylaxis For Hementioning
confidence: 99%
“…It was agreed that patients with a history of overt HE or treatment exposure should be excluded from these trials as treatment status has a significant confounding effect on the classification of neuropsychiatric performance. 34 Patients with overt HE may show few, if any, clinical abnormalities following treatment but retain some degree of neuropsychometric or neurophysiological impairment in the longer term. 3,35,36 These patients may be classified as having minimal HE but their responses to treatment will differ substantially from those diagnosed as having minimal HE de novo.…”
Section: Secondary Prophylaxis For Hementioning
confidence: 99%
“…Finally, previous studies have demonstrated that HE affects eye movements. Smooth pursuit eye movements are disrupted in conjunction with the degree of encephalopathy (Montagnese 2005), and a recent pilot study using saccadometry has shown increased saccadic latency in HE, correlating both with psychometric tests and flicker fusion performance (Krismer et al 2010). We therefore investigated whether the measurement of saccades might provide a novel quantitative neurological assessment for the diagnosis of CHE.…”
Section: Introductionmentioning
confidence: 98%
“…Somooth pursuit eye movements have been more recently shown to correlate with the degree of neurologic impariment, but their use is limited by the need for specialized equipment and head fixation (Montagnese et al 2005). …”
Section: Introductionmentioning
confidence: 99%